Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses Bulgaria's prospects for converging to the living standards of the more advanced members of the European Union (EU). The unfavorable economic environment of the early 1990s and the economic crisis in 1996-97 hurt Bulgaria's output, employment, and investment. Following the crisis, structural reforms and a sound macroeconomic framework set the stage for a sustained recovery. The structure of the Bulgaria economy has shifted markedly over the last decade, and investment has become the main engine of growth.